Genetic correlations between challenge tested susceptibility to bacillary necrosis, caused by Edwardsiella ictaluri, and growth performance tested survival and harvest body weight in Mekong striped catfish (Pangasianodon hypophthalmus) - Pham, Khoi Dinh (Journal of fish diseases, 2021)
© 2020 John Wiley & Sons Ltd.